2012
DOI: 10.1021/jm300259r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationships of Pyrazolo[1,5-a]pyridine Derivatives: Potent and Orally Active Antagonists of Corticotropin-Releasing Factor 1 Receptor

Abstract: Design, synthesis, and structure-activity relationships of a series of 3-dialkylamino-7-phenyl pyrazolo[1,5-a]pyridines (I) as selective antagonists of the corticotropin-releasing factor 1 (CRF(1)) receptor are described. The most prominent compound to emerge from this work, 46 (E2508), exhibits potent in vitro activity, excellent drug-like properties, and robust oral efficacy in animal models of stress-related disorders. It has advanced into clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…Here, we compared the effect of E2508 and diazepam on spontaneous locomotor activity in mice. As described above, E2508 shows significant anxiolytic effects in the light/dark test in BALB/c mice at 10 mg/kg [16].…”
Section: Effect Of E2508 and Diazepam On Spontaneous Locomotor Activimentioning
confidence: 62%
See 3 more Smart Citations
“…Here, we compared the effect of E2508 and diazepam on spontaneous locomotor activity in mice. As described above, E2508 shows significant anxiolytic effects in the light/dark test in BALB/c mice at 10 mg/kg [16].…”
Section: Effect Of E2508 and Diazepam On Spontaneous Locomotor Activimentioning
confidence: 62%
“…We previously reported that E2508 has a high affinity for the human (h) CRF1 receptor, with Ki values of 11.3 nM and >10 M for the hCRF1 and hCRF2 receptors, respectively [16]. In comparison, the reference compound, R121919, had a Ki value of 8.3 nM for the hCRF1 receptor.…”
Section: Inhibitory Effect Of E2508 and R121919 On Crf-induced Camp Pmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, much attention has been paid to pyridine and its derivatives due to their wide applications in different fields of medicine and material chemistry, most of which have potential biological activity [2,3 ]. There are two crystallographically independant moleculesinthe asymmetric unit of the title crystal structure, in which all bond lengths are within normal ranges.…”
Section: Discussionmentioning
confidence: 99%